A figura de Clitemnestra em Eurípides (Electra e Ifigénia em Áulide) - Brasete, Maria Fernanda
In this study, we intend to analyze the main euripidean marks of the characterization of Clytemnestra in two plays from the end of the fifth century BC. Based on the assumption that the tragic genre was rooted in the social reality of the "polis", the mythical themes of revenge, family conflict and war dramatized in intrigue constituted important cultural codes also in the design of secondary characters such us Clytemnestra. Thus, the focus of analysis focuses on the most distinctly differences in the tragic figurations of Clytemnestra in two euripidean plays, "Electra" and "Iphigenia at Aulis", which expressively renovate the mythic matrix, motivating the debate on political, ethical and moral dilemmas also commom to the Athenian society, at the time of the play's original production.